Financial and non-Financial Performance Analysis for Hotel Sustainability: A Case Study - PRAYOGI, I Gusti Bagus Raditya; YUSMARISA, Ni Luh Riska; JATMIKA, Aqmarina Ishmah; ROHMAN, Muhammad Rohid Abdur; PRAMESTI, Ayu Irmma Trisania (Journal of Governance, Taxation and Auditing, 2025)
This study aims to analyze financial ratios to assess the sustainability of PT Eastparc Hotel Tbk. The analysis was carried out by comparing financial statements from 2022 to 2024 using a descriptive quantitative method. The ratios used include liquidity, solvency, and profitability. The results of the analysis showed an increase in the liquidity ratio and a decrease in the solvency ratio, indicating that the financial structure is getting stronger. However, the profitability ratio has decreased from 2022 to 2024, so the efficiency of asset and capital use needs to be improved. In general, the value of the ratio is above the industry standard, indicating stable financial conditions. Based on this, management needs to improve the effectiveness of asset management and profit growth strategies for the company's sustainability. From the non-financial side, the company shows an excellent reputation. The company has shown sustained growth with attention to service quality and strengthening of its financial foundation to achieve sustainability.